Succession Planning for Libraries. Issue 7 (2nd October 2016) - Charbonneau, Deborah H.; Freeman, Jacqueline L.
ABSTRACT: It is imperative for libraries of all types to be responsive to the forecasted changes in the demographics of the library workforce. Succession planning is a key strategy for ensuring that libraries are prepared to meet changing and emerging organizational needs. Succession planning is broadly defined as a range of activities focused on both internal and external talent development to fill anticipated needs for library leadership and other key personnel. The aim of this article is to offer a number of recommendations relevant for LIS education to help build an awareness of succession planning for future library managers. In particular, practical ideas for course-related activities and assignments that may help to incorporate succession planning more fully into the LIS curriculum are discussed.